2017
DOI: 10.1016/j.jmii.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Improving dengue viral antigens detection in dengue patient serum specimens using a low pH glycine buffer treatment

Abstract: Inclusion of a low-pH glycine buffer treatment step in the commercially available Ag-ELISA is crucial for clinical diagnosis and E-containing viral particles could be a valuable target for acute DENV diagnosis, similar to NS1 detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this context, a number of developed immunosensors have shown excellent sensitivity. For example, Dias and co-workers reported 0.12 ng/mL while Cavalcanti and co-workers reported 0.33ng/mL limit of detection for their immunosensors, which is lower than 7ng/mL and 3.04 ng/mL limit of detection reported in some ELISA-based assays [ 73 , 74 ].…”
Section: Laboratory Diagnosis and Its Significancementioning
confidence: 87%
“…In this context, a number of developed immunosensors have shown excellent sensitivity. For example, Dias and co-workers reported 0.12 ng/mL while Cavalcanti and co-workers reported 0.33ng/mL limit of detection for their immunosensors, which is lower than 7ng/mL and 3.04 ng/mL limit of detection reported in some ELISA-based assays [ 73 , 74 ].…”
Section: Laboratory Diagnosis and Its Significancementioning
confidence: 87%
“…These complexes may hinder epitope recognition by anti-NS1 antibodies in the NS1 assay. Dissociation of these immune complexes by various pretreatment methods (for example, heat or acid treatment) has been shown to enhance the sensitivity of DENV NS1 assays [49,[51][52][53]. However, to our experiences, we observed that heat-or acid-pretreated specimens sometimes altered serotype-specific interpretation to be negative or cross reactive to other serotypes, possibly due to the disruption of epitopes recognized by conformation-dependent antibodies.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 47%
“…This is potentially due to the presence of NS1 immune complex (IC) which is generated by circulating NS1 and existing anti-NS1 antibodies [ 50 , 51 , 52 ] which reduces the amount of free NS1 protein. Disassociation of NS1 IC by heat or acid/base methods explored in previous studies [ 53 , 54 , 55 ] were found to enhance assay sensitivity. However, our NS1-Cygnus device and NS1-microplate ELISA gave above 82% sensitivity despite patient plasma used in this study being mostly from secondary infections (98%).…”
Section: Discussionmentioning
confidence: 94%